2006
DOI: 10.1007/s10802-006-9077-0
|View full text |Cite
|
Sign up to set email alerts
|

Is Theory of Mind Understanding Impaired in Males with Fragile X Syndrome?

Abstract: Males with fragile X syndrome (FXS) have difficulties with social interaction and many show autistic features. This study examines whether the social deficits characteristic of FXS stem from difficulties with theory of mind. Two groups of boys with FXS participated: a group with few autistic features and a group with many autistic features. An intellectual disability control group also participated. In addition to using standard theory of mind tasks, new techniques were used that were able to separate out the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 38 publications
1
26
0
Order By: Relevance
“…Individuals with ASD are known to struggle with abstract social concepts such as humor (Ozonoff & Miller, 1996) and the inability to appreciate jokes is thought to stem from impaired social understanding, which is core to ASD (Baron-Cohen, 1988; Siegal, Carrington, & Radel, 1996; Yirmiya, Erel, Shaked, & Solomonica-Levi, 1998). Social-cognitive impairments have also been documented among individuals with FXS (Grant, Apperly, & Oliver, 2007; Lewis et al, 2006; Losh, Martin, et al, 2012), and therefore similar performance in skills that rely on social understanding, such as humor signaling, might be expected in individuals with ASD-O as well as FXS-ASD. Given that shyness and anxiety are characteristic of FXS (Hagerman, 2002), perhaps the boys with FXS-ASD were less likely than those with ASD-O to become comfortable enough to joke with the examiner, resulting in less opportunities to exhibit inappropriate humor (participants who did not attempt to make any humorous remarks were not coded on this item by default).…”
Section: Discussionmentioning
confidence: 95%
“…Individuals with ASD are known to struggle with abstract social concepts such as humor (Ozonoff & Miller, 1996) and the inability to appreciate jokes is thought to stem from impaired social understanding, which is core to ASD (Baron-Cohen, 1988; Siegal, Carrington, & Radel, 1996; Yirmiya, Erel, Shaked, & Solomonica-Levi, 1998). Social-cognitive impairments have also been documented among individuals with FXS (Grant, Apperly, & Oliver, 2007; Lewis et al, 2006; Losh, Martin, et al, 2012), and therefore similar performance in skills that rely on social understanding, such as humor signaling, might be expected in individuals with ASD-O as well as FXS-ASD. Given that shyness and anxiety are characteristic of FXS (Hagerman, 2002), perhaps the boys with FXS-ASD were less likely than those with ASD-O to become comfortable enough to joke with the examiner, resulting in less opportunities to exhibit inappropriate humor (participants who did not attempt to make any humorous remarks were not coded on this item by default).…”
Section: Discussionmentioning
confidence: 95%
“…1 The youngest mean age that Apperly et al's (2004) FB task has been established is 13 years 3 months with a mean verbal mental age of 6 years 10 months in a sample of atypically developing children (including children with fragile X syndrome and intellectual disability; Grant, Apperly, & Oliver, 2007). Thus, children aged below 7 years and over 3 years were recruited.…”
Section: Methodsmentioning
confidence: 99%
“…According to some studies, the rate of autism and social avoidance behaviors increases with age in males with full mutation FXS (Hatton et al, 2006;Roberts et al 2007), while improvements in core symptomatology with age are typically identified in individuals with idiopathic ASD (Charman et al, 2005;Moss, Magiati, Charman & Howlin., 2008) A similar pattern of findings has emerged with regard to the identification of socio-cognitive characteristics including Theory of Mind (ToM). Although initial studies of individuals with FXS and ASD described deficits in ToM (Cornish et al, 2008) subsequent research has showed that a general information processing and working memory deficit may account for this poor performance in this area rather than a specific ToM deficit (Grant, Apperly & Oliver, 2007). These findings suggest that the subtle differences between ASD and FXS at the level of behavior may also be reflected at the level of social-cognition.…”
Section: Complexmentioning
confidence: 98%